Chronicle of a Summer - Rouch, Jean; Morin, Edgar; Morillière, Roger; Coutard, Raoul; Brault, Michel; Tarbès, Jean-Jacques (bfi, 2013)
One of the most influential documentaries ever made, "Chronicle of a Summer" put the term "cinéma-vérité" on the map and triggered debates about notions of "truth" in documentary filmmaking that remain all too valid today. In fact, one of the many fascinating things about this study of the lives and opinions of several inhabitants of Paris and Saint-Tropez in the summer of 1960 is the filmmakers’ scrupulous honesty - ethnographer Jean Rouch and sociologist Edgar Morin often appear on camera in order to discuss their aims with their subjects, and to show them the edited footage at the end to canvass their opinion about whether they were portrayed fairly (the results, perhaps not surprisingly, are inconclusive). [www.moviemail.com]